Changes in the acoustic behavior of resident bottlenose dolphins near operating vessels - Luís, Ana Rita (2014)
Maritime traffic is an issue of major ecological concern, and vessel noise may be an important source of disturbance for coastal cetaceans. In the Sado estuary, Portugal, core habitat areas of a small resident population of bottlenose dolphins (Tursiops truncatus) overlap with routes of intense maritime traffic, which presents an opportunity to assess vocal responses of these dolphins to specific vessel noise sources. Field recordings of dolphin vocalizations were made from April to November 2011, using a calibrated system. Dolphin behavior and group size were recorded, as well as the operating boat condition (no boats or specific boat type) in a 1,000 m radius. Spectral analyses of vocalizations allowed the categorization and quantitative analysis of echolocation click trains and social calls, including whistles. Mean overall call rates decreased significantly in the presence of operating vessels. Creaks (fast click trains) were significantly reduced in the presence of ferry boats. Significant differences were also observed in the whistles’ minimum, maximum, and start frequencies. These changes in call emission rates and temporary shifts in whistles characteristics may be a vocal response to the proximity of operating vessels, facilitating communication in this busy, noisy estuary.